Integrasi nilai-nilai moderasi beragama pada pembelajaran akidah akhlak - Rahmawati, Dwi; Subandi, Subandi; Jannah, Siti Roudhotul (Indonesian Journal of Educational Management and Leadership, 2023)
The purposes of this research are (1) to describe the values of religious moderation that are instilled in the teaching of the moral creed at MA Wali Songo; (2) to describe the process of inculcating religious moderation values in the teaching of aqidah morals at MA Wali Songo and (3) to analyze the impact of inculcating religious moderation values on the learning of aqeedah morals at MA Wali Songo. The approach used is qualitative with a case study type. The data collection technique are observation, interview adan documentation. The results of the study show that, (1) The values of religious moderation that are instilled in learning the Aqidah Akhlak are the values of tasamu or tolerance, I'tidal or fairness, and muwatanah; (2) The process of inculcating the values of religious moderation in the learning of the Akhlak Aqidah, namely, tasamuh values are carried out through learning, fair values are carried out by the aqidah moral teacher being an exemplary example, muwatanah values are carried out through apperception. Other efforts made by madrasas in instilling these values through several activities; (3) The impact of instilling the values of religious moderation in learning Aqidah Akhlak according to Aqidah Akhlak teachers still occurs in some students. Meanwhile, from the student side, the implementation of the values that have been instilled has been reflected.